2023
DOI: 10.3390/ijms24086939
|View full text |Cite
|
Sign up to set email alerts
|

Human Male Genital Tract Microbiota

Abstract: The human body is vastly colonised by microorganisms, whose impact on health is increasingly recognised. The human genital tract hosts a diverse microbiota, and an increasing number of studies on the male genital tract microbiota suggest that bacteria have a role in male infertility and pathological conditions, such as prostate cancer. Nevertheless, this research field remains understudied. The study of bacterial colonisation of the male genital tract is highly impacted by the invasive nature of sampling and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 112 publications
0
11
0
1
Order By: Relevance
“…The metagenomic reads generated from our samples had low proportion (< 0.5%) of unassigned reads indicating the power of the annotation analysis. Members of the phyla Pseudomonadota (formerly Proteobacteria), Bacillota (Firmicutes) and Actinomycetota were reported to dominate freshly collected urine using 16SrRNA-based urine microbiome study by (Nelson et al, 2010; Zuber et al, 2023). No phylum-level change and higher OTU-counts (not statistically significant) was observed in the stored urine than that of the fresh urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metagenomic reads generated from our samples had low proportion (< 0.5%) of unassigned reads indicating the power of the annotation analysis. Members of the phyla Pseudomonadota (formerly Proteobacteria), Bacillota (Firmicutes) and Actinomycetota were reported to dominate freshly collected urine using 16SrRNA-based urine microbiome study by (Nelson et al, 2010; Zuber et al, 2023). No phylum-level change and higher OTU-counts (not statistically significant) was observed in the stored urine than that of the fresh urine.…”
Section: Discussionmentioning
confidence: 99%
“…Above all, these differences are better captured via applying nucleic acid-based methods (Jung et al, 2019). With the emergence of culture-independent approaches and the subsequent human microbiome project (Turnbaugh et al, 2007), studies revealed the presence of a unique microbiota in the urinary tract system (reviewed in Zuber et al, 2023), the microbial structure and composition is also reported to be subject to change with age, sex and health status (Halinski et al, 2023, Pearce et al, 2014). Next-Generation Sequencing (NGS) targeting 16S rRNA was the most widely used approach to determine the bacterial portion of the urinary microbiome (Perez-Carrasco et al, 2021, Siddiqui et al, 2011, Lahr et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies performed so far have investigated the microbiota of the bladder or semen microbiome of post-massage urine in patients with pathologies such as PCa or infertility. 53,54 According to available evidence, seminal microbiota is associated with pathological states, such as viral infections (human immunodeficiency virus or human papillomavirus) or prostatitis. 53 A recent study demonstrated that symptoms of CP are associated with lesser microbial diversity of operational taxonomic units in semen and urine.…”
Section: Anatomical Peculiarities Of Pelvic Region and Cross-organ Se...mentioning
confidence: 99%
“…53,54 According to available evidence, seminal microbiota is associated with pathological states, such as viral infections (human immunodeficiency virus or human papillomavirus) or prostatitis. 53 A recent study demonstrated that symptoms of CP are associated with lesser microbial diversity of operational taxonomic units in semen and urine. 55 The proinflammatory effect of sperm dysbiosis is possible via the release of soluble factors, such as LPS, hemolysins, and other soluble spermatotoxic factors that can affect sperm physiology.…”
Section: Anatomical Peculiarities Of Pelvic Region and Cross-organ Se...mentioning
confidence: 99%
See 1 more Smart Citation